2018
DOI: 10.5603/gp.a2018.0042
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of IVF/ICSI success following treatment of endometriosis as the cause of primary infertility

Abstract: Therapy for endometriosis, AMH and P4 levels appeared to be predictors for the successful IVF/ICSI outcome and the use of long protocol with agonists could be advised in these cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…In addition, Billa et al 2018 reported a higher pregnancy rate in the surgery + ART group who received 3‐6 months of repressive therapies according to the stage of endometriosis rather than the surgery group who did not receive repressive therapy before ART (44% vs. 21%). They also had better results than in the ART alone group . This point may have not been considered in the studies evaluated in this meta‐analysis.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…In addition, Billa et al 2018 reported a higher pregnancy rate in the surgery + ART group who received 3‐6 months of repressive therapies according to the stage of endometriosis rather than the surgery group who did not receive repressive therapy before ART (44% vs. 21%). They also had better results than in the ART alone group . This point may have not been considered in the studies evaluated in this meta‐analysis.…”
Section: Discussionmentioning
confidence: 94%
“…All data about the authors, places and period of research, studies and diagnostic methods, treatment methods, and outcomes of research are given in Table …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations